Tourist Arrivals Increase, Hotel Occupancy Declines: Governance Strategies for Sustainable Tourism Accommodation in Bali - Agus Made Yoga Iswara; I Gusti Agung Ngurah Darma Suyasa; Ratu Agung Bagus Ngurah Putra; Putu Herny Susanti (Universitas Udayana, 2026)
Despite receiving approximately 6.9 million international tourist arrivals in 2025, Bali’s hotel occupancy remained relatively low at 57–67%, revealing governance challenges in the tourism accommodation sector. This disparity is partly driven by tourists’ growing preference for villas, homestays, and short-term rentals, many operating outside formal licensing and taxation systems. This study analyses the governance challenges underlying the mismatch between rising tourist arrivals and declining hotel occupancy and proposes strategies for sustainable tourism accommodation in Bali. Using a qualitative approach, data were collected through focus group discussions, semi-structured interviews, field observations, and analyses of policy documents and media reports. The findings show that the Bali Provincial Government and the Ministry of Tourism have strengthened regulatory enforcement, including restricting online travel agencies from marketing unlicensed accommodation providers. Although these measures have encouraged business formalization, non-compliance remains widespread. The study highlights the need for stronger enforcement, integrated data systems, and collaborative governance to foster a more accountable, competitive, and sustainable accommodation sector.